Digital Culture of the Individual as a Factor in the Socio-Psychological Safety of the Digital Space - M. E. Kudryavtseva; A. V. Pryakhina (Дискурс)
Introduction. The purpose of the article is to actualize the problem of the development of ideological transformations of modern society, determined by the new digital reality, as well as to determine the phenomenon of digital personal culture, its socio-psychological functions in a digital society, fixing the structure and content of each component.Methodology and sources. In their reflections, the authors relied on the works of the following researchers O.A. Grimov, V.I. Przhilensky, E.O. Trufanova, L.V. Baeva, I.I. Gorlova, A.L. Zorin, G.V. Soldatova, A.Yu. Kvitko, R.V. Belyaev and E.I. Grigorieva, M.I. Tsareva, etc. The empirical research carried out in the article was of a probing nature and was considered as preliminary, only outlining the paths of a possible deeper and more complete study. Thus, the article uses value and socio-psychological approaches. Analysis of a person’s digital culture from the standpoint of a value approach makes it possible to determine criteria for assessing the results of human social practices implemented in the digital space. The use of a socio-psychological approach makes it possible to determine the digital culture of an individual in the context of such phenomena as socialization and personal self-identification.Results and discussion. The most obvious discrepancies in the results of the questionnaire survey of different age groups were in those answers that were intended to determine the presence of an ontological component of a person’s digital culture. The legitimacy of the digital world as a different “mode of being” and a space for self-expression is recognized primarily by representatives of the younger age group, which is an alarming symptom. However, the greater level of responsibility in real life compared to digital life, which is recognized by representatives of all age groups, still allows us to speak about a certain expression of the ontological component. Also, the authors reveal a certain severity of the informational and communicative-ethical components of the digital culture of the individual.Conclusion. A more in-depth study, reliably obtained by the authors of the most general results, could be devoted to a deeper immersion in the development of individual aspects of individual authors of the components of the personality of digital culture, the study of the digital culture of individual age groups, the determination of connections between the personality of digital culture and its professional behavior and a number of other issues.